Frequency of masked hypertension in non-obese diabetics and obese diabetics - Kumar, Donakonda Arun; C. J., Tejeswini (International Journal of Research in Medical Sciences, 2017)
Background: Masked hypertension defined as clinic BP <140/90mmHg but home BP is in the hypertensive range of >135/85mmhg. It is an emerging clinical entity. Several risk factors, including sex, age, diabetes, obesity, smoking, have been associated with it. Masked hypertensives are usually under-treated and are at risk of cardiovascular complications. As the prevalence is high it is necessary to determine its frequency. Objectives was to evaluate the frequency of masked hypertension in non-obese diabetics and obese diabetics who had never been treated for hypertension. Methods: The study was carried out in JSS hospital, Mysore over a period of 2 years from 2014 to 2016. The study was designated as a comparative and exploratory study. 200 people each of non-obese diabetics and obese diabetics were selected based on inclusion and exclusion criteria. Clinic SBP and DBP was recorded and self-monitoring automatic BP apparatus was given to record home SBP and DBP. Each patient was categorized into either of the four groups normotension, sustained hypertension, masked hypertension and white coat hypertension. Results: Frequency of masked hypertension among non-obese diabetics and obese diabetics is 16% and 20% respectively. Average clinic SBP, DBP home SBP and DBP among non-obese diabetics with masked hypertension are 133.06, 83.15, 139.06 and 84.45 respectively when compared to normotensive which are 113.44, 71.46, 109.81, 70.86 respectively (significant p value of <0.0001). Average clinic SBP, DBP home SBP and DBP among obese diabetics with masked hypertension are 135.60, 84.13, 140.63, and 86.93 respectively when compared to normotensive which are 117.80, 74.10, 115.59, 72.71 respectively (significant p value of <0.0001). Conclusions: In summary, present study demonstrated frequency of masked hypertension among non-obese diabetics and obese diabetics was higher when compared with other studies done on general population. There are no studies done on masked hypertension among obese and non-obese diabetics for proper comparison of data from current study. As the frequency is higher in both non-obese diabetic and obese diabetic groups in current study it signifies the importance of recording the home blood pressures to detect masked hypertension.